FISH INDUSTRY: A DISCOURSE ANALYSIS OF THE FUTURE PERSPECTIVE OF PAKISTAN - SHAHZAD, SM (Biological and Clinical Sciences Research Journal, 2022)
The research article outlines Pakistan's fisheries industry output from 1950 to the recent past and fishery product trading from 1980 to 2011. Based on economic research, the findings show that fish output and export continuously rose year after year. Despite this, the pace of development in fish output over the previous two decades has been quite modest compared to other emerging nations. The research also shows that inland aquaculture output in Pakistan is quickly outpacing marine aquaculture. On the contrary, no marine aquaculture methods exist or are supported to improve fish output. The article discusses and measures fisheries sector security and future development potential for coastal and non-coastal regions. In Pakistan, aquaculture has emerged as the most promising option to address fish demand, food security, livelihood, employment, and national GDP. Furthermore, it is critical to focus on marine aquaculture to restore marine fishing resources, which may generate livelihoods in coastal communities. Finally, the main idea of this article is to provide developmental techniques for authorities to grow and expand the aquaculture industry, which might provide numerous options for livelihood support in Pakistan. The research uses methodological triangulation to evaluate the on-ground reality from a broader perspective. Moreover, an online survey will be presented to evaluate the output of the fish industry of Pakistan.